Changes in N-terminal glucagon-like immunoreactivity and insulin during short-term gluten challenge in childhood coeliac disease. Issue 7 (July 1981) - Carson, D J; Glasgow, J F; Buchanan, K D; Sloan, J M
Abstract : Sixteen patients (aged 3.5-14.3 years) with normal jejunal mucosa, originally diagnosed as having coeliac disease at least 18 months before, were started on gluten challenge. The 'end point' of challenge was significant deterioration in jejunal mucosa morphologically and morphometrically. Studies carried out both before and after challenge included intestinal absorption of D-xylose and glucose, and release of insulin and N-terminal glucagon-like immunoreactivity (N-GLI). After gluten challenge, there were significant increases in plasma N-GLI at both 45 (P less than 0.05) and 120 minutes (P less than 0.03) after oral glucose. Significant reduction occurred in glucose absorption at 45 minutes (P less than 0.04), in one-hour D-xylose absorption (P less than 0.01) and fasting serum cholesterol (P less than 0.01). Plasma N-GLI showed significant negative correlations with D-xylose absorption (P less than 0.003) and serum cholesterol (P less than 0.004).